2017
DOI: 10.5301/ijao.5000620
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Low-dose Thalidomide in Refractory Gastrointestinal Bleeding in Left Ventricular Assist Device Patients

Abstract: Thalidomide appears to be a safe and effective option for management of refractory LVAD-related GIB. Monitoring for recurrent GIB should be performed closely following cessation of thalidomide therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Prospective, randomized, and larger studies are underway to confirm these results (NCT01707225). Thalidomide and danazol also seem to decrease recurrent bleeding, 25–28 to be confirmed by prospective and larger studies. Recently, a pilot study reported a significant reduction of blood transfusions, bleeding‐related hospitalizations, and endoscopy procedures in LVAD's patients with refractory GI angiodysplasia related bleeding after intravenous infusion of a humanized monoclonal antibody against VEGF (bevacizumab Avastin) 29 .…”
Section: Discussionmentioning
confidence: 76%
“…Prospective, randomized, and larger studies are underway to confirm these results (NCT01707225). Thalidomide and danazol also seem to decrease recurrent bleeding, 25–28 to be confirmed by prospective and larger studies. Recently, a pilot study reported a significant reduction of blood transfusions, bleeding‐related hospitalizations, and endoscopy procedures in LVAD's patients with refractory GI angiodysplasia related bleeding after intravenous infusion of a humanized monoclonal antibody against VEGF (bevacizumab Avastin) 29 .…”
Section: Discussionmentioning
confidence: 76%
“…Both somatostatin and octreotide inhibit GI bleeding by increasing platelet aggregation, decreasing splanchnic blood flow, downregulating the formation of vascular endothelial growth factor and increasing GI vascular bed resistance 38). Thalidomide has also been used to treat angiodysplasias in LVAD patients because of its anti-angiogenic effects 39). Another option for medical therapy is digoxin which inhibits HIF-1α synthesis 40).…”
Section: Complications Of Lvadsmentioning
confidence: 99%
“…In patients with refractory or recurrent GI-bleeding or in whom a lesion cannot be localized or treated by endoscopy, others approaches might be discussed according to the “2-hit model: these aiming to prevent or eradicate angiodysplasias and/or those aiming to reduce or prevent HMW-multimers defect. Data supporting the use of antiangiogenic drugs, mostly octreotide (52, 7073) and thalidomide (7476), are sparse and mostly limited to case reports and retrospective single-center studies. In constitutional VWD, recurrent GI-bleeding is an indication to start prophylaxis with intravenous infusion of VWF concentrates.…”
Section: Therapeutic Options For Bleeding Management Of Vad-patients:mentioning
confidence: 99%